(untitled) (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2020)
One of the important roles of the seagrass ecosystem is as a carbon sink from the atmosphere. Bintan Island is an area that has a fairly extensive seagrass ecosystem. This study aims to estimate the carbon content of seagrass beds from all types of seagrass and sediments in the waters of Berakit and Dompak, Bintan Island. Determination of potential carbon stock is carried out by looking at the estimated carbon stock in the sediment and biomass of seagrass including the upper part (leaves and midrib) and the bottom of the seagrass (rhizome and roots). Measurement of carbon stock in seagrass sediments was carried out using the dry ashing method (LOI) and the carbon content in seagrass biomass was measured using the conversion method using a constant. The results showed that at the Berakit station the estimated total carbon stock of sediment was 91 Mg Corg ha-1 and 10.58 Mg C/m2 for the estimation of seagrass carbon content, while the Dompak station estimated total carbon stock in the sediment ranged from 103.80 Mg Corg ha-1 and 3.34 Mg C/m2 to estimate the carbon content of seagrass parts. The carbon content in the substrate is influenced by the sediment composition and the carbon content in the seagrass is influenced by the density of the seagrass.